-8x-40=7c-12+13x

Simple and best practice solution for -8x-40=7c-12+13x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-40=7c-12+13x equation:


Simplifying
-8x + -40 = 7c + -12 + 13x

Reorder the terms:
-40 + -8x = 7c + -12 + 13x

Reorder the terms:
-40 + -8x = -12 + 7c + 13x

Solving
-40 + -8x = -12 + 7c + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
-40 + -8x + -13x = -12 + 7c + 13x + -13x

Combine like terms: -8x + -13x = -21x
-40 + -21x = -12 + 7c + 13x + -13x

Combine like terms: 13x + -13x = 0
-40 + -21x = -12 + 7c + 0
-40 + -21x = -12 + 7c

Add '40' to each side of the equation.
-40 + 40 + -21x = -12 + 40 + 7c

Combine like terms: -40 + 40 = 0
0 + -21x = -12 + 40 + 7c
-21x = -12 + 40 + 7c

Combine like terms: -12 + 40 = 28
-21x = 28 + 7c

Divide each side by '-21'.
x = -1.333333333 + -0.3333333333c

Simplifying
x = -1.333333333 + -0.3333333333c

See similar equations:

| 0.19x=1.52 | | X/6-9=-8 | | 3X+5Y=550 | | 12X+2Y=517 | | -6x+4=5x+14-13x | | 4x-8/3=4 | | 4x+3=10-3x | | 12-(1/3)= | | 6x+35=-x | | 8x+9=12x-5 | | 6v+14=8v+24 | | 12-1/3= | | -2x+1-(-3x+3)=-4+(x-2) | | 12r=18(r+.5) | | -5x+2=10-8x | | r=6(r+.5) | | .3333x+5=.16666(2x-5) | | 12x-3y-10= | | Inx-in(x+3)=6 | | Y/3-y=4 | | 6(2x+4)=8x-3 | | r=6(2r+1) | | -2(3x-1)-4x=5x-(3x-6) | | -12n-(4n+5)=16-3n | | -10-bracket(-7)+2= | | 1/6×5= | | 3/2=3x-4/7 | | -8-(8)= | | 1/6×5 | | y-4x+110=0 | | x^2-9x+y^2=0 | | 7x^2-448= |

Equations solver categories